The Role of the Center for Dialogue and Cooperation Among Civilizations (CDCC) in the Framework of Strengthening a Free Public Space - Amir Fiqi (The International Journal of Politics and Sociology Research, 2021)
After the fall of the authoritarian New Order and the formation of a new era, namely the era of reformation, a free public space is open to the public by providing a place for the public to express their freedom and autonomy in the form of freedom of the press, freedom of parties, freedom of common sense, freedom of belief, freedom of expression. sense, freedom to defend oneself, freedom to defend community, regional autonomy, independence, and freedom to gather for discussion and dialogue. The role played by the CDCC is to facilitate a free and independent public space for citizens with different religious or cultural backgrounds to speak, discuss and dialogue to discuss religious issues and even state problems in order to criticize and control the government in order to form good governance. In conducting dialogue, the CDCC takes elite segments of society such as religious leaders, government circles, activists and culturalists, not grassroots communities. Even though they take the elite segment, they are not elitist because the meetings (dialogues) held by the CDCC always discuss issues related to the interests of the lower classes who are always excluded from the policies produced by the government. The CDCC is also concerned with dialogues related to religion and belief by always holding meetings between followers of different religions in order to create a pluralist and tolerant society. As a form of implementing the role of the CDCC in efforts to establish a free public space in the life of society and the state, the CDCC conducts a dialogue or discussion.